The Silent Communication of Penghayat Kepercayaan: Identity Negotiation and Co-cultural Strategies in a Muslim-Majority Community - Ramadhan, Hafizh Faikar Agung; Menzelthe, Caecilia; Novianti, Wiwik; Widjanarko, Wisnu; Sutikna, Nana (Postgraduate, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
This research highlights the paradox of pluralism in Indonesia, where Penghayat Kepercayaan (indigenous faith practitioners) frequently employ defensive communication strategies despite having constitutional guarantees. This study aims to analyze the phenomenon of 'Silent Communication' within the Paguyuban Budaya Bangsa (PBB) community in Kebumen as a mechanism for identity negotiation amidst a Muslim-majority society. Utilizing a qualitative collective case study approach framed by Co-Cultural Theory and Impression Management, this research dissects how minority groups construct communication boundaries. The findings demonstrate that this community adopts 'Pseudo-Administrative Affiliation' and 'Digital Silence' as primary survival strategies. Furthermore, the study identifies an internal 'Spiral of Silence' within the organization that obstructs leadership regeneration and reveals that the younger generation continues to practice self-censorship in digital spaces despite achieving legal recognition. This research concludes that minority silence is not merely a cultural trait but a structural response to social insecurity, necessitating an ethical shift from the majority group to foster inclusive dialogue. Moreover, the Muslim community—theologically anchored by the principles of la ikraha fiddin (no compulsion in religion), qaulan layyinan (gentle speech), and haqqul jawar (the rights of neighbors)—is challenged to actualize these values in daily practice, spanning administrative policies, social interactions, and digital media ethics.